Advanced Insights into The Role of Food Processing, Fortification and Antinutritional Factors on Iron Absorption - Tyagi, Khushi; Kohli, Vedika; Sikka, Khushi; Kumari, Meena (Journal of Neonatal Surgery, 2025)
Iron deficiency remains a widespread global health concern, particularly in populations consuming predominantly plant-based diets, where iron bioavailability is often compromised due to the presence of antinutritional factors. This systematic review evaluates the effectiveness of various strategies to enhance iron bioavailability, focusing on food processing methods, iron fortification, and the impact of dietary inhibitors. Using the PRISMA methodology, relevant studies were systematically identified, screened, and analysed. The review examines the influence of different food processing techniques, including heat processing, germination/malting, milling, soaking, and fermentation, in reducing the inhibitory effects of phytates, polyphenols, and tannins. These methods have been shown to modify food matrices, improve iron solubility, and enhance its absorption. The role of iron fortification is also examined, with a focus on selecting appropriate iron compounds and incorporating complementary dietary strategies that facilitate better iron uptake. Additionally, the review investigates the impact of antinutritional factors dietary fiber, phytates, polyphenols, tannins, and lectins on iron absorption and discusses strategies to mitigate their effects. The findings from the analysed studies highlight the importance of optimizing food processing techniques and fortification strategies to improve dietary iron availability. The review concludes by summarizing the results of three key research questions, offering insights that can guide dietary recommendations and nutritional strategies for addressing iron deficiency.